Effect of Different Environmental Conditions on Durabilities of Polyester- and Vinylester-Based Glass-Fiber-Reinforced Polymer Pultruded Profiles - Yang, Shulan; Chu, Mingkun; Chen, Fangyi; Fu, Miaorui; Lv, Yiwen; Xiao, Ziyi; Feng, Ningning; Song, Yang; Li, Jiannan (Frontiers in Materials, 2022)
This paper presents the results of experimental investigations on the durability of glass-fiber-reinforced polymer (GFRP) pultruded profiles made of unsaturated polyester (UP) and vinylester (VE) resins commonly used in civil engineering. The water absorption, tensile properties, and microstructures of GFRP profiles exposed to several typical accelerated aging environments (e.g., deionized water, salt water, salt fog, and combined hygrothermal cycles) for 12 months were investigated. Moreover, a sustained loading factor was included in the test to reflect the behavior of the GFRP profiles in real structures. A normalization approach based on the controlled specimens was used to assess the effectiveness and relevance of the accelerated exposure. The results indicated that the maximum moisture absorption of both UP and VE GFRP profiles was immersed in deionized water, where the masses increased by 1.03 and 0.53%, respectively, leading to the maximum degradation of tensile strength (24.03%) of UP GFRP profile immersion in deionized water after 360 days of aging. However, the tensile modulus was more sensitive to high temperatures and has the maximum degradation (47.03%) after hygrothermal cycles. Moreover, VE GFRP profiles show superior humidity and temperature endurance. Furthermore, the sustained loading exacerbated the degradation of tensile properties slightly under the same conditions. Finally, by incorporating the cumulative damage caused by the sustained loading and a time-dependent factor into a residual strength model, a revised model was proposed to describe the tensile strength loss of pultruded UP GFRP profiles.